Modul Berbasis Logika Pembuktian untuk Mengurangi Level Abstraksi Topik Grup dan Sifat-Sifatnya - Defri Ahmad; Fridgo Tasman; Ronal Rifandi; Saddam Al Aziz; Rara Shandy Winanda (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
The most essential thing in mathematics is proof, it makes mathematics being different with other subjects. One of subject in mathematics that always need prove to understand the concept is abstract algebra. In studying abstract algebra, student need various abstract concepts to include in its concepts. It is hard for student to understand the structures in abstract algebra and prove some of mathematical object that satisfy the structures. Group and its properties is the first structure in abstract algebra that has an abstract concept. It is hard for student to understand some objects, that is proven satisfy a structure and why the proof steps just flow. By giving explanation and reason in every proofing step, we try to increase student proving level and reduce the abstraction level of the concepts. To see how this module reduces the abstraction level in teaching group, this module is applied to university students and evaluated by interviewing and questionnaires to the students. Base on student response and by some perspectives, student proving ability increase and the abstraction level of the concept is diminished in some aspects.